Effects of cupping therapy for obesity: A protocol for systematic review and meta-analysis. Issue 44 (5th November 2021) - Kim, Hyungsuk; Kim, Koh-Woon; Chung, Won-Seok
Abstract: Background: Obesity is a prevalent disease in modern society. Despite the various interventions available in conventional medicine, their success rates are not satisfactory because of the complex mechanisms involved in obesity. Cupping therapy is a traditional Chinese medicinal intervention, and it has become widely used in various clinical settings for the treatment of obesity. This systematic review and meta-analysis will investigate the effects of cupping on obesity. Methods: Three Korean databases (KoreaMed, Oriental Medicine Advanced Searching Integrated System, and ScienceON), 1 Japanese database (Citation Information by the National Institute of Informatics), 1 Chinese database (Chinese National Knowledge Infrastructure), MEDLINE/PubMed, EMBASE, and The Cochrane Central Register of Controlled Trials will be searched for studies published until March 2021. The primary outcome is body weight. The secondary outcomes will be body mass index, waist-hip ratio, waist circumference, hip circumference, body fat mass, body fat percentage, and adverse events. Results: This systematic review and meta-analysis will evaluate the effects of cupping therapy for obesity. Conclusion: The results of this systematic review and meta-analysis will then be discussed in a related journal for clinicians working with obese patients to apply the interventions in this article. Trial registration number: DOI 10.17605/OSF.IO/P8JVM (https://osf.io/p8jvm ).